Insertion-and-deletion-derived tumour-specific neoantigens and the immunogenic phenotype: a pan-cancer analysis. Issue 8 (August 2017) - Turajlic, Samra; Litchfield, Kevin; Xu, Hang; Rosenthal, Rachel; McGranahan, Nicholas; Reading, James L; Wong, Yien Ning S; Rowan, Andrew; Kanu, Nnennaya; Al Bakir, Maise; Chambers, Tim; Salgado, Roberto; et al.
Summary: Background: The focus of tumour-specific antigen analyses has been on single nucleotide variants (SNVs), with the contribution of small insertions and deletions (indels) less well characterised. We investigated whether the frameshift nature of indel mutations, which create novel open reading frames and a large quantity of mutagenic peptides highly distinct from self, might contribute to the immunogenic phenotype. Methods: We analysed whole-exome sequencing data from 5777 solid tumours, spanning 19 cancer types from The Cancer Genome Atlas. We compared the proportion and number of indels across the cohort, with a subset of results replicated in two independent datasets. We assessed in-silico tumour-specific neoantigen predictions by mutation type with pan-cancer analysis, together with RNAseq profiling in renal clear cell carcinoma cases (n=392), to compare immune gene expression across patient subgroups. Associations between indel burden and treatment response were assessed across four checkpoint inhibitor datasets. Findings: We observed renal cell carcinomas to have the highest proportion (0·12) and number of indel mutations across the pan-cancer cohort (p<2·2 × 10 −16 ), more than double the median proportion of indel mutations in all other cancer types examined. Analysis of tumour-specific neoantigens showed that enrichment of indel mutations for high-affinity binders was three times that of non-synonymous SNV mutations. Furthermore, neoantigens derived from indel mutations were nine times enriched for mutant specific binding, as compared with non-synonymous SNV derived neoantigens. Immune gene expression analysis in the renal clear cell carcinoma cohort showed that the presence of mutant-specific neoantigens was associated with upregulation of antigen presentation genes, which correlated ( r =0·78) with T-cell activation as measured by CD8-positive expression. Finally, analysis of checkpoint inhibitor response data revealed frameshift indel count to be significantly associated with checkpoint inhibitor response across three separate melanoma cohorts (p=4·7 × 10 −4 ). Interpretation: Renal cell carcinomas have the highest pan-cancer proportion and number of indel mutations. Evidence suggests indels are a highly immunogenic mutational class, which can trigger an increased abundance of neoantigens and greater mutant-binding specificity. Funding: Cancer Research UK, UK National Institute for Health Research (NIHR) at the Royal Marsden Hospital National Health Service Foundation Trust, Institute of Cancer Research and University College London Hospitals Biomedical Research Centres, the UK Medical Research Council, the Rosetrees Trust, Novo Nordisk Foundation, the Prostate Cancer Foundation, the Breast Cancer Research Foundation, the European Research Council.